Tanggung Jawab PT. Telkom Indonesia (Persero), Tbk Atas Layanan Jasa Indonesia Digital Home - Anggi Safitri Sutan Syafli; Theresia Louize Pesulima; Ronald Fadly Sopamena (PATTIMURA Law Study Review, 2023)
In Law Number 8 of 1999 concerning Consumer Protection and Book III of the Civil Code concerning Binding which regulates the agreement relationship involving one party and the other party in order to obtain a legal certainty for the losses that will be experienced in the future, but in the case of network disruptions in PT Telkom's Indihome service, there have been internet interruptions in the Indihome service for several days and made consumers feel disadvantaged. This makes consumers question the responsibility of PT Telkom in handling the problem of internet interference. The research method used is juridical, namely research on legal rules, norms and principles based on laws and regulations, which are related to the problems studied. The type of research used is Descriptive Analysis on the grounds that the results used from the literature study are then analyzed and discussed using the flow of discussion systematically in several chapters. And the sources of legal material are Primary, Secondary and Tertiary. As well as legal material collection techniques using literature studies, analysis of legal materials using qualitative methods. The results showed that PT Telkom Indonesia, Tbk has a legal position if PT Telkom Indonesia, Tbk acts as a victim in this case, but in the case studied by the author, it is the consumer who is the victim in this problem where the consumer can report PT Telkom Indonesia, Tbk if the consumer meets the requirements to submit a request to the court in accordance with the meaning of legal position. And PT Telkom Indonesia, Tbk can be responsible for implementing a service level guarantee, which is an obligation of PT Telkom Indonesia, Tbk to consumers, which starts with PT Telkom Indonesia, Tbk resolving consumer problems within one month in accordance with applicable regulations, but if within one month PT Telkom Indonesia, Tbk cannot resolve the problem, PT Telkom Indonesia, Tbk is required to compensate consumers. The reason PT Telkom Indonesia, Tbk is responsible for the losses suffered by consumers is because Indihome is a subsidiary of PT Telkom Indonesia, Tbk.